Phonological Complexity in the Japanese Short Poetry: Coexistence Between Nearest-Neighbor Correlations and Far-Reaching Anticorrelations - Hayata, Kazuya (Frontiers in Physics, 2018)
Sound correlations among six sites on the Japanese short poetry are analyzed in detail. For haiku composed of 5-7-5 syllables, the six sites are occupied by the head vowels on the three phrases as well as by the end sounds (in addition to five vowels, a syllabic nasal being included) on them. For tanka, first, one should divide the entire poem (5-7-5-7-7 syllables) into two parts, namely, the first (5-7-5) and the latter (5-7-7) part. For the six-dimensional array of sounds, there are 203 rhyme patterns possible. Specifically, for corpora of the haiku poetry, the complete works of three haiku poets, all of whom are distinguished in Japan, are selected. For those of the tanka, Collection of Ten Thousand Leaves and The Twenty-One Collections of Waka are chosen. Analyzed results through comparison between the surveyed and the expected frequencies show statistically the strong preference for the arrangements with a far-reaching antirhyming between sounds on the three ends, along with the correlation between those on the heads. In addition to the avoided rhyming, one finds a preference for specific arrangements exhibiting the nearest-neighbor correlations. Subsequently, to manifest the distinctive feature of each corpus, correlation analysis is carried out between frequency distributions of the arrangements. Moreover, in order to explore a statistical rule for the rank-ordered data, fitting is attempted to a long-tail distribution, followed by the Durbin-Watson testing. Quantitative analyses by using Gini's coefficient as well as Shannon's information entropy are also made. Finally, it is shown that the results of the complicated rhyming can be explained in part in comparison with the sound correlation between the first and the latter parts in the full names of Japanese.